1995
DOI: 10.2337/diab.44.7.810
|View full text |Cite
|
Sign up to set email alerts
|

31P–Nuclear Magnetic Resonance Evidence of an Activated Hexose-Monophosphate Shunt in Hyperglycemic Rat Lenses In Vivo

Abstract: Using 31P-nuclear magnetic resonance spectroscopy, we have identified elevated concentrations of sedoheptulose-7-phosphate (S-7-P) in lenses from three animal models of hyperglycemia: streptozotocin-induced diabetic rats, galactose-fed rats, and xylose-fed rats. This observation provides a unique and independent confirmation of the activation of the hexose monophosphate shunt (HMPS) pathway in the hyperglycemic lens in vivo. While the elevation in concentration of S-7-P was very dramatic, the other HMPS metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Although these metabolites are thought to be potential precursors of pentosidine (49), our previous experiments showed that products from fructose-3-phosphate and 3-DG reacted with antibodies to CML (18), which suggests that these agents are possible (although not likely principal) sources of CML as well. The increased polyol pathway flux may further accentuate the pentose phosphate pathway as a consequence of a reduced NADPH/NADP ϩ ratio (50), which leads to marked elevation in the level of sedoheptulose-7-phosphate, which is another reactive intermediate (51). We found that products from sedoheptulose-7-phosphate and BSA were also definitely reactive to the anti-CML antibodies (Y.H., et al, unpublished data).…”
Section: Hamada and Associatesmentioning
confidence: 82%
“…Although these metabolites are thought to be potential precursors of pentosidine (49), our previous experiments showed that products from fructose-3-phosphate and 3-DG reacted with antibodies to CML (18), which suggests that these agents are possible (although not likely principal) sources of CML as well. The increased polyol pathway flux may further accentuate the pentose phosphate pathway as a consequence of a reduced NADPH/NADP ϩ ratio (50), which leads to marked elevation in the level of sedoheptulose-7-phosphate, which is another reactive intermediate (51). We found that products from sedoheptulose-7-phosphate and BSA were also definitely reactive to the anti-CML antibodies (Y.H., et al, unpublished data).…”
Section: Hamada and Associatesmentioning
confidence: 82%
“…In 1990, Szwergold et al [41] reported the identification of fructose 3-phosphate in the lens of diabetic rats, and recently, two studies described the presence of a kinase converting fructoselysine to fructoselysine 3-phosphate [42,43]. Fructoselysine 3-phosphate appears to decom- pose into free lysine, inorganic phosphate and 3-deoxyglucosone [43].…”
Section: Fructosamine Kinasementioning
confidence: 99%
“…These considerations argued against a role of 'fructose 3-kinase' in fructose metabolism, and led us to postulate that the physiological substrate of this kinase was not fructose itself, but compounds with a closely related structure, possibly fructosamines. This was further supported by an abstract suggesting the presence in human erythrocytes of a kinase acting on fructose and glycated histones [24].…”
Section: A Model Fructosamine Inhibits the Formation Of Fructose 3-phmentioning
confidence: 91%